Application of polymerization inhibitor in photosensitive and developing solder resist ink, photosensitive and developing solder resist ink

CN122978769APending Publication Date: 2026-10-27GUANG DONG SQ UV CURING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611236781.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0007]本发明的目的在于,提供可用于感光显影阻焊油墨的铜基配合物阻聚剂,不仅解决现有铜基配合物作为阻聚剂存在的技术问题;而且解决现有技术中以滑石粉作为感光显影阻焊油墨的填料时,现有阻聚剂用量过高容易降低油墨的曝光感度、油墨光固化反应不足、显影质量变差的技术问题

Benefits of technology

(1)本发明以可聚合的铜基配合物作为阻聚剂,在含有滑石粉的A组分中具有显著阻聚稳定功能,抑制体系凝胶。而且,该配合物阻聚剂在紫外光辐照下,经光化学反应,其阻聚功能明显减弱或消失,有利于油墨感光区域的光固化进行,间接提高油墨曝光区域感度,性能显著优于传统阻聚剂MEHQ。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_15
    Figure SMS_15
  • Figure SMS_17
    Figure SMS_17
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The application discloses application of a polymerization inhibitor in a photosensitive developing solder resist ink, the polymerization inhibitor is a copper-based complex containing a methacrylic acid group, has a significant polymerization inhibition stability function in an A component containing talcum powder, inhibits system gelation, and under ultraviolet light irradiation, the polymerization inhibitor is subjected to a photochemical reaction, the polymerization inhibition function of the polymerization inhibitor is obviously weakened or disappears, the photo-curing of the photosensitive area of the ink is facilitated, the photosensitivity of the exposed area of the ink is indirectly improved, and side effects are avoided. The application further discloses the photosensitive developing solder resist ink, the photosensitive developing solder resist ink adds the polymerization inhibitor into the A component, improves the storage stability of the A component system in the ink, and increases the photosensitivity of the ink.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ink technology, specifically relating to the application of polymerization inhibitors in photosensitive solder resist inks and photosensitive solder resist inks. Background Technology

[0002] Two-component liquid photoimageable solder mask (LPIM) is a core material for achieving high-precision solder mask patterning in PCB manufacturing. It consists of a main agent (component A) and a curing agent (component B) that are separately packaged and stored and mixed before use. It has both liquid photosensitive imaging and thermosetting crosslinking properties and is widely used in high multilayer boards, HDI, IC substrates and substrate-like boards (SLP) and other fields.

[0003] Component A comprises five functional modules: oligomers containing carboxyl and acrylate groups provide an alkali-soluble development framework and photocuring reaction sites; multifunctional acrylate monomers dilute viscosity and construct a photocrosslinking network; a photoinitiator system uses a synergistic combination of type I pyrolysis initiators (Irgacure 184, TPO, 819) and type II hydrogen-abstracting initiators (benzophenone, ITX, and amine co-initiator EDAB) to match the 365-405 nm exposure band; inorganic fillers (talc, molten SiO2, BaSO4) to regulate CTE and enhance solderability and chemical resistance; and coloring pigments to achieve light-shielding and optical recognition. Component B, the curing agent system, contains bisphenol A epoxy resin or phenolic epoxy resin as the thermosetting body, which can be catalyzed by polyetheramine or imidazole to open the carboxyl-epoxy ring-opening esterification, forming a secondary crosslinking network. Additives include dispersants, leveling agents, defoamers, adhesion promoters, and thixotropic agents (vaporized SiO2) to ensure application performance.

[0004] The preparation of solder resist ink includes a pre-baking stage, a photosensitive stage, a developing stage, and a post-baking stage. The pre-baking stage (80-120℃) aims to evaporate solvents and achieve leveling. The photosensitive stage is the core of patterning. In the exposed areas, the photoinitiator breaks down to produce free radicals (Type I) or abstracts hydrogen to produce free radicals (Type II), initiating the growth and cross-linking of acrylate chains; in the unexposed areas, the polymerization inhibitor needs to remain dormant to suppress the dark reaction caused by scattered light and oxygen diffusion. The developing stage dissolves the carboxyl resin in the unexposed areas, and the post-baking stage achieves carboxyl-epoxy ring-opening esterification, forming a dense thermosetting network.

[0005] Polymer inhibitors are key regulators of the storage stability and pattern accuracy of LPISM. Their core function in the pre-baking stage is to inhibit thermally initiated polymerization; in the photosensitive stage, they rapidly fail in the exposed area and efficiently inhibit polymerization in the non-exposed area. Among existing polymer inhibitors, quinone inhibitors interfere with ink color; nitrile radical inhibitors are expensive, yellowing, and require a dissociation temperature >120℃, making them suitable for high-end chemically amplified adhesives and precision carriers. MEHQ (4-methoxyphenol) is commonly used as a phenolic polymer inhibitor for the A component of two-component liquid photosensitive solder resist inks to prevent acrylate polymerization and gelation during storage. MEHQ terminates free radicals through phenolic hydroxyl hydrogen transfer. It has low volatility, good thermal stability, and low cost, but its polymerization inhibition efficiency is relatively weak. While talc as a filler offers advantages such as significantly reducing cost while ensuring ink heat resistance and adjusting thixotropy for easier screen printing, it also presents the technical problem of talc-induced acrylate polymerization leading to gelation and shortened ink storage time. In this process, conventional polymer inhibitors are difficult to effectively inhibit polymerization. While significantly increasing the proportion of MEHQ can suppress the gelation of component A, it will reduce the exposure sensitivity of the final ink, resulting in insufficient ink photocuring reaction and poor development quality.

[0006] In the prior art, copper-based complexes rely on Cu 2+ / Cu + Redox cycles achieve catalytic polymerization inhibition, and a single copper ion can continuously terminate multiple free radical chains, with an efficiency 3-4 times higher than that of phenols. However, copper-based complexes have the following problems as polymerization inhibitors for photosensitive solder resist inks: (1) Copper-based complexes may induce early cross-linking of carboxyl and epoxy groups in the solder resist ink, resulting in incomplete development. For example, although copper-based polydentate complexes such as Cu(acac)2 can reduce the catalytic side effects of carboxyl-epoxy reactions, the volatilization of dissociated ligands after photosensitive exposure can easily lead to pinhole defects in the ink. (2) Conventional copper complexes lack constraints on the migration of copper ions, which may lead to copper ion aggregation (including reduction aggregation), resulting in poor insulation of the ink layer. Therefore, it is urgent to find new ink polymerization inhibitors. Summary of the Invention

[0007] The purpose of this invention is to provide a copper-based complex polymerization inhibitor that can be used in photosensitive solder resist inks. This not only solves the technical problems existing with copper-based complexes as polymerization inhibitors, but also solves the technical problems in the prior art where, when talc is used as a filler in photosensitive solder resist inks, excessive use of the existing polymerization inhibitor can easily reduce the ink's exposure sensitivity, cause insufficient photocuring reaction, and deteriorate the developing quality.

[0008] According to a first aspect of the present invention, the application of a polymerization inhibitor in photosensitive solder resist ink is provided, wherein the polymerization inhibitor is a copper-based complex with the structural formula shown in Formula 1: Formula 1, Wherein, R represents an alkylene group with 2 to 5 carbon atoms, an alkylene group with 2 to 5 carbon atoms containing a methyl branch, an alkylene group with 2 to 5 carbon atoms containing an ether bond, or an alkylene group with 2 to 5 carbon atoms containing an ester bond.

[0009] The polymerization inhibitor of this invention is a β-dicarbonyl copper complex containing a methacrylate structure. It possesses methacrylate groups capable of participating in polymerization and a copper chelate structure, which imparts polymerization inhibition to the complex. This inhibitor is soluble in organic solvents and acrylate monomers. In photosensitive solder resist ink formulations, it replaces traditional phenolic polymerization inhibitors, extending the storage time of talc-containing ink component A and inhibiting significant viscosity increases and gelation. During UV exposure, the inhibitory activity is neutralized through the complex's own photosensitivity reaction, promoting photopolymerization and curing. Furthermore, the polymerization of the methacrylate groups immobilizes the chelated ligands within the polymer crosslinking network, inhibiting the aggregation of copper atoms / ions and preventing the side effect of reduced ink insulation caused by copper ion migration and aggregation during photosensitivity.

[0010] The present invention selects copper complexes containing methacrylate groups as polymerization inhibitors instead of copper complexes containing acrylate groups as polymerization inhibitors, mainly because the active methylene group in the β-dicarbonyl structure can easily undergo Michael addition with acrylate, thereby destroying the stability of the ligand and coordination compound.

[0011] In some embodiments, R represents an alkylene group having 2 to 4 carbon atoms or an alkylene group having 2 to 4 carbon atoms containing a methyl branch.

[0012] In some embodiments, the polymerization inhibitor has the following structural formula: , or .

[0013] In some embodiments, the polymerization inhibitor is prepared by the following steps: S1. Mix hydroxyalkyl methacrylate with an organic base catalyst to obtain a first mixture. Heat the mixture to 50-70°C and add diketene to the first mixture. React for 5-7 h. Cool and purify the product after the reaction to obtain acetyl acetoxyalkyl methacrylate. S2. Dissolve copper acetate monohydrate in an organic solvent to obtain a copper acetate solution, and dissolve alkyl acetyl methacrylate in an organic solvent to obtain an alkyl acetyl methacrylate solution; then add the alkyl acetyl methacrylate solution to the copper acetate solution to obtain a mixed solution, adjust the pH of the mixed solution to 6.8-7.0, react for 6-8 h, then age the mixed solution to obtain crystals, purify, and obtain the final product.

[0014] The polymerization inhibitor of the present invention reacts hydroxyalkyl methacrylate with diketene at low temperature with high efficiency to form an esterification structure, thereby obtaining a methacrylate coordinating monomer (AAXMA) containing a β-dicarbonyl group. The β-dicarbonyl structure of this monomer reacts with copper acetate monohydrate to efficiently synthesize a chelated coordination structure (Cu(AAXMA)2).

[0015] In some embodiments, the hydroxyalkyl methacrylate is selected from at least one of hydroxyethyl methacrylate, 4-hydroxybutyl methacrylate, and 2-hydroxypropyl methacrylate.

[0016] In some embodiments, the molar ratio of hydroxyalkyl methacrylate to diketene is 1:(1~1.2). Preferably, the molar ratio of hydroxyalkyl methacrylate to diketene is 1:1.1.

[0017] In some embodiments, the organic base catalyst is selected from at least one of 4-dimethylaminopyridine (DMAP), triethylamine, and 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU).

[0018] In some embodiments, the organic solvent is anhydrous ethanol.

[0019] In some embodiments, the molar ratio of copper acetate monohydrate to acetyl acetoxymethyl methacrylate is 1.0:(2.0~3.0). Preferably, the molar ratio of copper acetate monohydrate to acetyl acetoxymethyl methacrylate is 1.0:(2.0~2.2).

[0020] In some embodiments, in step S1, the purification method involves washing and extracting the reaction product with a 5% hydrochloric acid solution, retaining the organic phase, then washing the organic phase with water and extracting until the pH of the aqueous phase reaches 6.8-7.0, and finally drying the organic phase. The purpose of washing with hydrochloric acid solution is to remove unreacted excess diketene, organic base catalyst, and other hydrophilic byproducts; the purpose of washing with water is to further remove the above-mentioned alkaline impurities.

[0021] In other embodiments, the organic phase is dried by using a desiccant, filtering, and retaining the organic phase. The desiccant is selected from at least one of anhydrous magnesium sulfate and anhydrous sodium sulfate.

[0022] In some embodiments, in step S2, ammonia is used to adjust the pH of the mixed solution to 6.8-7.0. The mass fraction of the solute in the ammonia is 1%. Adjusting the pH of the mixed solution to 6.8-7.0 by adding ammonia promotes the coordination reaction between copper acetate and acetyl acetoxymethyl methacrylate.

[0023] In some embodiments, in step S2, the aging method is to age the mixed solution at 4-6°C for 24 hours, filter it, and obtain crystals.

[0024] In some embodiments, in step S2, the purification method involves washing the crystals 2-3 times with anhydrous ethanol, followed by vacuum drying. The purpose of washing with anhydrous ethanol is to remove unreacted copper salts and alkyl acetyl methacrylates.

[0025] According to a second aspect of the present invention, a photosensitive solder resist ink is provided, comprising, by weight, separately packaged components A and B, wherein component A comprises 100-110 parts of an oligomer containing carboxyl and acrylate groups, 5-7 parts of a photoinitiator, 10-15 parts of an acrylate monomer, 20-25 parts of talc, and 0.03-0.05 parts of a polymerization inhibitor; and component B comprises 4-8 parts of an epoxy curing agent. The polymerization inhibitor is a copper-based complex, and its structural formula is shown in Formula 1: Formula 1, wherein R represents an alkylene group having 2 to 5 carbon atoms, an alkylene group having 2 to 5 carbon atoms with a methyl branch, an alkylene group having 2 to 5 carbon atoms with an ether bond, or an alkylene group having 2 to 5 carbon atoms with an ester bond.

[0026] The photosensitive solder resist ink of this invention uses the aforementioned polymerization inhibitor and talc as raw materials, which can significantly reduce costs while improving the heat resistance of the final ink. The polymerization inhibitor not only plays a role in preventing polymerization by talc-induced acrylate polymerization and extending the ink's shelf life, but also provides the ink's exposure sensitivity, ensuring sufficient photocuring reaction and improved development quality. The polymerizable β-dicarbonyl copper complex of this invention can avoid defects such as ink pinholes that occur during post-baking.

[0027] In some embodiments, the content of the polymerization inhibitor in component A is 50-500 ppm. Preferably, the content of the polymerization inhibitor in component A is 50-300 ppm. More preferably, the content of the polymerization inhibitor in component A is 100-300 ppm.

[0028] In some implementations, the talc powder has a mesh size of 3000 to 6000.

[0029] In some embodiments, the epoxy curing agent is bisphenol A epoxy resin or phenolic epoxy resin. Specifically, the epoxy curing agent is selected from at least one of 128 epoxy resin, E-44 epoxy resin, and E-35 epoxy resin. Preferably, the epoxy curing agent is 128 epoxy resin.

[0030] In some embodiments, the acid value of the oligomer containing carboxyl and acrylate groups is 40-120 mgKOH / g.

[0031] In some embodiments, the acrylate monomer is selected from at least one of trimethylolpropane triacrylate (TMPTA), tripropylene glycol diacrylate (TPGDA), and 1,6-hexanediol diacrylate (HDDA).

[0032] In some embodiments, component A further includes 3-4 parts of defoamer, 3-4 parts of organic solvent, 1-2 parts of colorant, 0.3-0.6 parts of dicyandiamide, and 2-3 parts of melamine. Dicyandiamide and melamine act as latent catalysts in the post-thermo-curing process of ink. At higher temperatures, they can catalyze the reaction between carboxyl groups and epoxy groups in the ink, resulting in more complete ink curing and better overall performance.

[0033] The beneficial effects of this invention are as follows: (1) The present invention uses a polymerizable copper-based complex as a polymerization inhibitor, which has a significant polymerization inhibition and stabilizing function in component A containing talc, and inhibits the gelation of the system. Moreover, under ultraviolet light irradiation, the polymerization inhibitor of this complex undergoes a photochemical reaction, and its polymerization inhibition function is significantly weakened or disappears, which is conducive to the photocuring of the photosensitive area of ​​the ink, and indirectly improves the sensitivity of the exposed area of ​​the ink. Its performance is significantly better than that of the traditional polymerization inhibitor MEHQ.

[0034] (2) Compared with non-polymerizable β-dicarbonyl copper complexes (copper acetylacetone Cu(acac)2, ethyl acetoacetate copper Cu(EAA)2), the polymerizable β-dicarbonyl copper complex of the present invention can polymerize under light conditions to form a polymer network ligand structure, which complexes and fixes copper ions and cuprous ions generated by photoreduction, inhibits their migration, thereby reducing the side effects in the later stage. It can suppress the ink discoloration problem in the exposure, development and post-baking process, and also avoid the defects such as ink pinholes and oil eddies in the post-baking process. Detailed Implementation

[0035] The present invention will be described in further detail below, but the embodiments of the present invention are not limited thereto. The raw materials and reagents involved in the following examples are all commercially available.

[0036] In this invention, the polymerization inhibitor is a copper-based complex with the structural formula shown in Formula 1: Formula 1, Wherein, R represents one of the following: an alkylene group having 2 to 5 carbon atoms, an alkylene group having 2 to 5 carbon atoms with a methyl branch, an alkylene group having 2 to 5 carbon atoms with an ether bond, or an alkylene group having 2 to 5 carbon atoms with an ester bond.

[0037] For example, alkylene groups with 2 to 5 carbon atoms can be -CH2-CH2-, -CH2-CH2-CH2-, -CH2-CH2-CH2-CH2-, or -CH2-CH2-CH2-CH2-CH2-. Alkylene groups with 2 to 5 carbon atoms containing methyl branches can be -CH(CH3)-CH2-, -CH(CH3)-CH2-CH2-, -CH2-CH(CH3)-CH2-, -CH(CH3)-CH2-CH2-CH2-, or -CH2-CH(CH3)-CH2-CH2-. Alkylene groups with 2 to 5 carbon atoms containing ether bonds can be -CH2-O-CH2-, -CH2-O-CH2-CH2-, or -CH2-CH2-O-CH2-CH2-. The alkylene groups containing ester bonds with 2 to 5 carbon atoms can be -CH2-COO-CH2-, -CH2-COO-CH2-CH2-, or -CH2-CH2-COO-CH2-CH2-.

[0038] In this invention, Cu(acac)2 is a copper complex formed by acetylacetone (acac) and copper with a molecular weight of 263.8; Cu(AAEA)2 is a copper complex formed by ethyl acetoacetate (EAA) and copper with a molecular weight of 323.8.

[0039] 4-Hydroxybutyl methacrylate, CAS number 997-46-6, has the following structural formula: .

[0040] 2-Hydroxypropyl methacrylate, CAS number 923-26-2, has the following structural formula: .

[0041] The 128 epoxy resin is NPEL-128 (Nan Yat Group, Taiwan), with an epoxy equivalent of 184-190 g / eq.

[0042] Example 1 This embodiment provides a method for preparing the complex Cu(AAEMA)2, including the following steps: (1) 26.03 g (0.20 mol) of hydroxyethyl methacrylate (HEMA) and 0.03 g of 4-dimethylaminopyridine (DMAP) were added to a three-necked flask. A reflux condenser, a dropping funnel, and a magnetic stirrer were attached. 17.65 g of diketene (redistilled and purified, 0.21 mol) was added to the dropping funnel. The three-necked flask was stirred and heated to 60°C. Then, diketene was slowly added dropwise to the three-necked flask (about 1 drop / 3 seconds). After the addition of diketene was completed, the reaction was stirred at 60°C for another 6 hours to obtain a reaction solution. After the reaction was completed, the mixture was cooled and the reaction solution was washed and extracted with 5% dilute hydrochloric acid to separate the aqueous layer and the organic phase. The organic phase was washed with water and extracted until the pH of the aqueous layer was close to neutral. The organic phase was separated and collected and dried overnight with anhydrous magnesium sulfate. The solid anhydrous magnesium sulfate was removed by filtration to obtain the product AAEMA, with a yield of 93%.

[0043] (2) Take 50 mL of anhydrous ethanol into a 100 mL three-necked flask, install a thermometer, reflux condenser, and magnetic stirrer, add 1.99 g of copper acetate monohydrate to the three-necked flask, heat and stir in an oil bath at 50℃ for 30 minutes until a blue transparent solution appears, thus obtaining a copper acetate solution. Take another beaker, dissolve 4.28 g of AAEMA in 20 mL of anhydrous ethanol, stir to dissolve, and obtain a pale yellow homogeneous solution. Transfer the AAEMA solution into a dropping funnel. At room temperature, slowly add the AAEMA solution to the copper acetate solution using a dropping funnel at a rate of about 1 drop / 3 seconds, completing the addition in 2 hours. During the addition, the solution color can be observed to change from blue to blue-green, becoming slightly turbid. The temperature should be controlled not to exceed 30℃ throughout the addition process, and a cold water bath should be used for cooling if necessary. After the addition is complete, slowly add dilute ammonia water (1% concentration) to the three-necked flask to adjust the pH to about 7.0. The solution can be observed to gradually become clear and turn a deep blue-green. After adjusting the pH, continue stirring the solution at room temperature for 6 hours. Stop stirring, transfer the solution to a brown bottle, and age it at 5°C for 24 hours, resulting in the precipitation of blue-green crystals. Filter and collect the crystals, washing 2-3 times with 10 mL of cold anhydrous ethanol (approximately 5°C) each time to remove unreacted copper salts and free AAEMA. Transfer the crystals to a vacuum drying oven and dry for 8 hours to obtain a blue-green powdery product, with a yield of 88%.

[0044] AAEMA can be observed at 3500 cm⁻¹ using infrared spectroscopy. -1 There are no hydroxyl absorption peaks nearby, at 1750, 1722, and 1715 cm⁻¹. -1 Three peaks corresponding to the ketone carbonyl and ester carbonyl groups appear at 1635 and 940 cm⁻¹. -1 The characteristic peak corresponding to the carbon-carbon double bond of the acrylate appeared at [a specific location]. These results indicate that ethyl acetoacetoxymethacrylate was successfully synthesized from HEMA via an ester addition reaction with diketene.

[0045] Elemental analysis of Cu(AAEMA)₂ revealed a C content of 49.1% (theoretical value 48.8%), a hydrogen content of 5.8% (theoretical value 5.7%), and a copper content of 12.9% (theoretical value 13.0%), consistent with the elemental composition of Cu(AAEMA)₂. Compared to the raw material AAEMA, the infrared spectrum of Cu(AAEMA)₂ showed a higher concentration in the 1600-1580 cm⁻¹ range. -1 and 1530 cm -1 The characteristic peak at 1635 cm⁻¹ is a newly appearing strong peak, confirming the formation of a chelate ring through enol coordination; -1 The retention of the double bond peak at the specified position indicates that the carbon-carbon double bond of the methacrylate remains intact. The maximum absorption wavelength of the product Cu(AAEMA)₂ in dichloromethane solution is 332 nm. These experimental results demonstrate the successful synthesis of Cu(AAEMA)₂, with the structural formula shown below: .

[0046] Cu(AAEMA)2 crystals are sensitive to ultraviolet light and will change color upon prolonged exposure to sunlight. When heated to approximately 200℃, they will undergo a thermal decomposition reaction, accompanied by thermal polymerization and hardening; therefore, they must be stored away from light.

[0047] The synthetic route of AAEMA in Example 1 is shown below: .

[0048] Example 2 This embodiment provides a method for preparing the complex Cu(AABMA)2, including the following steps: (1) Add 31.5 g (0.20 mol) of 4-hydroxybutyl methacrylate (4-HBMA) and 0.03 g of 4-dimethylaminopyridine (DMAP) to a three-necked flask, attach a reflux condenser, a dropping funnel and a magnetic stirrer, and add 17.65 g of diketene (redistilled and purified, 0.21 mol) to the dropping funnel. Turn on the stirring in the three-necked flask and heat it to 60°C. Then slowly add diketene to the three-necked flask (about 1 drop / 3 seconds). After the diketene is added, continue stirring at 60°C for 6 hours to obtain the reaction solution. After the reaction was completed and cooled, the reaction solution was washed and extracted with 5% dilute hydrochloric acid to separate the aqueous layer and the organic phase. The organic phase was washed with water and extracted until the pH of the aqueous layer was near neutral. The aqueous layer was separated and discharged. The organic phase was washed with water and extracted until the pH of the aqueous layer was near neutral. The organic phase was separated and collected. The organic phase was dried with anhydrous magnesium sulfate overnight. The anhydrous magnesium sulfate solid was removed by filtration to obtain the product AABMA with a yield of 95%.

[0049] (2) Take 50 mL of anhydrous ethanol into a 100 mL three-necked flask, install a thermometer, reflux condenser, and magnetic stirrer, add 1.99 g of copper acetate monohydrate to the flask, heat and stir in an oil bath at 50°C for 30 minutes until a blue transparent solution appears, obtaining a copper acetate solution. Separately, take a beaker and dissolve 5.13 g of AABMA in 20 mL of anhydrous ethanol, stirring until dissolved to obtain a pale yellow homogeneous solution. Transfer the AABMA solution to a dropping funnel. At room temperature, slowly add the AABMA solution dropwise to the copper acetate solution using the dropping funnel at a rate of approximately 1 drop / 3 seconds, completing the addition in 2 hours. During the addition, the solution color can be observed to change from blue to blue-green, becoming slightly turbid. The temperature must be controlled to not exceed 30°C throughout the addition process; if necessary, use a cold water bath for cooling and temperature control. After the addition is complete, slowly add dilute ammonia (1% concentration) to the three-necked flask to adjust the pH to approximately 7.0. The solution will gradually become clear, turning a deep blue-green. After adjusting the pH, continue stirring the solution at room temperature for 6 hours. Stop stirring, transfer the solution to a brown bottle, and age it at 5°C for 24 hours, resulting in the precipitation of blue-green crystals. Filter and collect the crystals, washing 2-3 times with 10 mL of cold anhydrous ethanol (approximately 5°C) each time to remove unreacted copper salts and free AABMA. Transfer the crystals to a vacuum drying oven and dry for 8 hours to obtain a blue-green powdery product with a yield of 85%.

[0050] Cu(AABMA)2 crystals are hygroscopic and should be stored in a sealed, light-protected container. The structural formula is shown below: .

[0051] AABMA can be detected using infrared spectroscopy at a depth of 3500 cm. -1 There are no hydroxyl absorption peaks nearby, at 1748, 1720, and 1716 cm⁻¹. -1 Three peaks corresponding to the ketone carbonyl and ester carbonyl groups appear at 1634 and 940 cm⁻¹. -1 The characteristic peak corresponding to the carbon-carbon double bond of the acrylate appeared at [a specific location]. These results indicate that 4-acetylacetoxy-butyl methacrylate was successfully synthesized from diketene via an ester addition reaction.

[0052] Elemental analysis of Cu(AABMA)₂ revealed that the product's elemental composition includes C, H, and Cu, similar to that of Example 1 and consistent with the elemental composition of Cu(AABMA)₂. Compared to the raw material AABMA, the infrared spectrum of Cu(AABMA)₂ shows a higher concentration of C in the 1600-1580 cm⁻¹ range. -1 and 1530 cm -1The characteristic peak at the [location] is a newly appearing strong peak, confirming the formation of a chelate ring through enol coordination; simultaneously, the double bond peak is retained, proving that the carbon-carbon double bond of the methacrylate remains. The maximum absorption wavelength of the product Cu(AABMA)2 in dichloromethane solution is 332 nm. These experimental results indicate that Cu(AABMA)2 was successfully synthesized.

[0053] The synthesis route of AABMA in Example 2 is shown below: .

[0054] Example 3 This embodiment provides a method for preparing the complex Cu(AAPMA)2, including the following steps: 28.8 g (0.20 mol) of 2-hydroxypropyl methacrylate (HPMA) and 0.03 g of 4-dimethylaminopyridine (DMAP) were added to a three-necked flask. A reflux condenser, a dropping funnel, and a magnetic stirrer were attached. 17.65 g of diketene (redistilled and purified, 0.21 mol) was added to the dropping funnel. The three-necked flask was stirred and heated to 60 °C. Diketene was then slowly added dropwise (approximately 1 drop / 3 seconds) until the addition was complete. The mixture was then stirred at 60 °C for another 6 hours to obtain the reaction solution. After the reaction was complete, the mixture was cooled and washed with 5% dilute hydrochloric acid. The organic phase was dried overnight with anhydrous magnesium sulfate. The anhydrous magnesium sulfate solid was removed by filtration to obtain the product AAPMA, with a yield of 87%.

[0055] (2) Take 50 mL of anhydrous ethanol into a 100 mL three-necked flask, install a thermometer, reflux condenser, and magnetic stirrer, add 1.99 g of copper acetate monohydrate to the three-necked flask, heat and stir in an oil bath at 50℃ for 30 minutes until a blue transparent solution appears, thus obtaining a copper acetate solution. In a separate beaker, dissolve 4.84 g of AAPMA in 20 mL of anhydrous ethanol, stir to dissolve, and obtain a pale yellow homogeneous solution. Transfer the AAPMA solution into a dropping funnel. At room temperature, slowly add the AAPMA solution to the copper acetate solution using a dropping funnel at a rate of about 1 drop / 3 seconds, completing the addition in 2 hours. During the addition, the solution color can be observed to change from blue to blue-green, becoming slightly turbid. The temperature should be controlled not to exceed 30℃ throughout the addition process, and a cold water bath should be used for cooling if necessary. After the addition is complete, slowly add dilute ammonia water (1% concentration) to the three-necked flask to adjust the pH to about 7.0. The solution can be observed to gradually become clear and dark blue-green. After adjusting the pH, continue stirring the solution at room temperature for 6 hours. Stop stirring, transfer the solution to a brown bottle, and age it in a refrigerator at 5°C for 24 hours, precipitating blue-green crystals. Filter and collect the crystals, washing 2-3 times with 10 mL of cold anhydrous ethanol each time to remove unreacted copper salts and free AAPMA. Transfer the crystals to a vacuum drying oven and dry for 8 hours to obtain a blue-green powder product, with a yield of 86%.

[0056] Cu(AAPMA)2 crystals should be stored away from light.

[0057] AAPMA can be detected using infrared spectroscopy at a depth of 3500 cm. -1 No hydroxyl absorption peaks were observed nearby, and three peaks corresponding to the ketone carbonyl and ester carbonyl groups, as well as the characteristic peaks corresponding to the carbon-carbon double bonds of the acrylate, were also observed. These results indicate that AAPMA was successfully synthesized from HPMA via an ester addition reaction with diketene, and its structural formula is shown below: .

[0058] Elemental analysis of Cu(AABMA)₂ revealed that the product's elemental composition includes C, H, and Cu, similar to that of Example 1 and consistent with the elemental composition of Cu(AABMA)₂. Compared to the raw material AABMA, the infrared spectrum of Cu(AABMA)₂ shows a higher concentration of C in the 1600-1580 cm⁻¹ range. -1 and 1530 cm -1 The characteristic peak at the [location] is a newly appearing strong peak, confirming the formation of a chelate ring through enol coordination; simultaneously, the double bond peak is retained, proving that the carbon-carbon double bond of the methacrylate remains. The maximum absorption wavelength of the product Cu(AABMA)2 in dichloromethane solution is 332 nm. These experimental results indicate that Cu(AABMA)2 was successfully synthesized.

[0059] The synthesis route of AAPMA in Example 3 is shown below: .

[0060] Table 1 shows the basic formulation of photosensitive solder resist ink, in which the mass of the polymerization inhibitor is 0.02% of the total mass of the formulation.

[0061] The photosensitive developing resin is SQH resin, which is produced by Guangdong Sanqiu Photocurable Materials Technology Co., Ltd. This resin is obtained by modifying phenolic epoxy acrylate resin with tetrahydrophthalic anhydride. It is an oligomer containing carboxyl groups and acrylate structures, with an acid value of 45 mgKOH / g, a solid content of 60%, and DBE solvent, which is mixed divalent carboxylic acid dimethyl ester.

[0062] Table 1. Basic Formulation of Photosensitive Solder Resist Ink

[0063] Photosensitive solder resist inks for Application Examples 1-3 and Comparative Examples 1-3 were prepared using Cu(AAEMA)2, Cu(AABMA)2, Cu(AAPMA)2, p-methoxyphenol MEHQ, copper acetylacetone Cu(acac)2 and ethyl acetoacetate copper Cu(EAA)2 as polymerization inhibitors, according to the formulations in Table 1.

[0064] The preparation method of photosensitive developing solder resist ink is as follows: weigh and mix each raw material to obtain component A, component B and polymerization inhibitor respectively. Mix component A and polymerization inhibitor evenly. When curing is required, mix component A and component B evenly to obtain the final product.

[0065] The following tests and performance evaluations will be conducted.

[0066] 1. Antigel stability test of polymerization inhibitor on component A of photosensitive solder resist ink According to the basic formulation of photosensitive solder resist ink shown in Table 1, weigh and mix the raw materials to obtain component A and the polymerization inhibitor. After mixing component A and the polymerization inhibitor evenly, use a rotational viscometer to test the viscosity η0 of component A at 25°C. Place component A in a 60°C oven and let it stand for 7 days. Take a sample to observe whether gelation occurs. If no gelation occurs, test its viscosity η1 at 25°C and compare this viscosity value with the initial viscosity value. Calculate the percentage increase in viscosity according to the following formula: The rate of change in viscosity of component A upon heating (%) = .

[0067] 2. Evaluation of the effect of polymerization inhibitors on the photosensitivity of inks Photosensitive solder resist ink was screen-printed onto a clean copper-clad laminate and pre-baked at 80°C for 60 minutes to remove solvent, resulting in a non-cured dry film. A 21-level grayscale exposure scale was then applied, and the film was exposed on a standard exposure machine according to standard specifications. The film was then rinsed and developed with a 1% sodium carbonate aqueous solution. The ink exposure residue was checked, and the weakest exposure sensitivity (the higher the number, the lower the transmitted light intensity and the better the sensitivity) and the development resolution linewidth were read.

[0068] 3. Evaluation of appearance performance after baking The post-baking appearance performance evaluation is based on the exposure and development of the photosensitive solder resist ink, followed by baking at 150℃ for 60 minutes, and then observing whether there are pinholes on the surface of the cured ink.

[0069] 4. Volume resistivity test Replace the copper-clad laminate with a pure copper plate, prepare a sample using the method described above to obtain the ink cured on the copper plate, and measure the volume resistivity of the photosensitive solder resist ink according to standard GB / T1410-2006.

[0070] The test results of each photosensitive solder resist ink are shown in Table 2. Table 2 shows that the photosensitive solder resist ink containing talc, with MEHQ added as a polymerization inhibitor, exhibited gelation after 7 days at 60°C. This indicates that the amount of MEHQ at this concentration is insufficient to prevent the gelation of component A in the photosensitive solder resist ink, which is detrimental to its storage. In contrast, the photosensitive solder resist inks of Examples 1-3 and Comparative Examples 2-3, with the same amount of polymerization inhibitor, did not exhibit gelation after 7 days, and the change in thermal viscosity was 4.8%-8.7%. This indicates that a small amount of copper complex added as a polymerization inhibitor can achieve good polymerization inhibition in the photosensitive solder resist ink.

[0071] From the perspective of ink exposure sensitivity, the ink exposure sensitivity of the photosensitive solder resist inks of Application Examples 1-3 is higher than that of the inks of Comparative Examples 1-3, increasing from level 12 to level 13. This indicates that the photosensitive solder resist inks prepared by using Cu(AAEMA)2, Cu(AABMA)2, and Cu(AAPMA)2 as polymerization inhibitors have better photosensitivity than MEHQ or copper complexes without double bonds. This may be because the polymerization inhibitors of Examples 1-3 of the present invention contain methacrylate groups that can participate in photopolymerization, and β-dicarbonyl chelated copper can be photolyzed under photosensitivity to reduce the polymerization inhibition effect, and even generate certain active free radicals to initiate polymerization.

[0072] In terms of the resolvable linewidth, the smallest resolvable linewidth after exposure of the ink in Comparative Example 1 is 12 micrometers, the smallest resolvable linewidth after exposure of the ink in Comparative Example 2 is 11 micrometers, the smallest resolvable linewidth after exposure of the inks in Application Examples 1, 2, and 3 is 10 micrometers, and the smallest resolvable linewidth after exposure of the ink in Application Example 3 is 9 micrometers. These results indicate that photosensitive solder resist inks prepared using Cu(AAEMA)2, Cu(AABMA)2, and Cu(AAPMA)2 as polymerization inhibitors have better resolution.

[0073] From the perspective of post-baking appearance performance evaluation, pinholes can be observed on the ink surface of Comparative Example 2 and Comparative Example 3 after post-baking, while no pinholes are observed on the ink surface of Application Examples 1-3 and Comparative Example 1 after post-baking. This indicates that the present invention uses Cu(AAEMA)2, Cu(AABMA)2, and Cu(AAPMA)2 as polymerization inhibitors to prepare photosensitive solder resist inks, eliminating the technical defects of pinholes and oil swirls that occur in the post-baking stage when Cu(acac)2 and Cu(EAA)2 are used as solder resists to prepare photosensitive solder resist inks.

[0074] From the perspective of ink volume resistivity, the volume resistivity of the photosensitive solder resist inks of Application Examples 1 to 3 is close to that of the ink of Comparative Example 1, and higher than that of the photosensitive solder resist inks using Cu(acac)2 and Cu(EAA)2 as solder resistants. Among them, the volume resistivity of the inks of Application Examples 1 and 2 is on the same order of magnitude as that of the ink of Comparative Example 1, indicating that the change of the polymerization inhibitor has little effect on the ink volume resistivity.

[0075] In summary, using Cu(AAEMA)2, Cu(AABMA)2, and Cu(AAPMA)2 as polymerization inhibitors to prepare photosensitive solder resist inks, compared to inks prepared using MEHQ, Cu(AAEMA)2, Cu(AABMA)2, and Cu(AAPMA)2, not only provides better polymerization inhibition performance and significantly extends the ink's shelf life, but also inhibits the viscosity increase of ink component A induced by talc as a filler. Furthermore, under the film covering the ink's inhibition surface, the polymerization inhibitor can be photodeactivated, promoting photocuring of the ink in the exposed area and avoiding a reduction in the ink's exposure sensitivity and development quality.

[0076] Table 2 Test results of various photosensitive solder resist inks

[0077] The above descriptions are merely some embodiments of the present invention. Those skilled in the art can make various modifications and improvements without departing from the inventive concept of the present invention, and these all fall within the scope of protection of the present invention.

Claims

1. The application of polymerization inhibitors in photosensitive solder resist inks, characterized in that, The polymerization inhibitor is a copper-based complex, and its structural formula is shown in Formula 1: Formula 1, Wherein, R represents an alkylene group with 2 to 5 carbon atoms, an alkylene group with 2 to 5 carbon atoms containing a methyl branch, an alkylene group with 2 to 5 carbon atoms containing an ether bond, or an alkylene group with 2 to 5 carbon atoms containing an ester bond.

2. The application according to claim 1, characterized in that, In Formula 1, R represents an alkylene group with 2 to 4 carbon atoms or an alkylene group with 2 to 4 carbon atoms containing a methyl branch.

3. The application according to claim 1 or 2, characterized in that, The structural formula of the polymerization inhibitor is , or .

4. The application according to claim 1, characterized in that, The polymerization inhibitor is prepared by the following steps: S1. Mix hydroxyalkyl methacrylate with an organic base catalyst to obtain a first mixture. Heat the mixture to 50-70°C and add diketene to the first mixture. React for 5-7 hours. Cool and purify the product after the reaction to obtain acetyl acetoxyalkyl methacrylate. S2. Dissolve copper acetate monohydrate in an organic solvent to obtain a copper acetate solution, and dissolve alkyl acetyl methacrylate in an organic solvent to obtain an alkyl acetyl methacrylate solution; then add the alkyl acetyl methacrylate solution to the copper acetate solution to obtain a mixed solution, adjust the pH of the mixed solution to 6.8-7.0, react for 6-8 h, age the mixed solution to obtain crystals, purify, and obtain the final product.

5. The application according to claim 4, characterized in that, The molar ratio of hydroxyalkyl methacrylate to diketene is 1:(1.0~1.2); the molar ratio of copper acetate monohydrate to acetyl acetoxyalkyl methacrylate is 1.0:(2.0~3.0).

6. The application according to claim 1 or 4, characterized in that, The hydroxyalkyl methacrylate is selected from at least one of hydroxyethyl methacrylate, 4-hydroxybutyl methacrylate, and 2-hydroxypropyl methacrylate; the organic base catalyst is selected from at least one of 4-dimethylaminopyridine, triethylamine, and 1,8-diazabicyclo[5.4.0]undec-7-ene; and the organic solvent is anhydrous ethanol.

7. The application according to claim 4, characterized in that, In step S1, the purification method is as follows: the product after reaction is washed and extracted with a 5% hydrochloric acid solution, the organic phase is retained, the organic phase is then washed with water and extracted until the pH of the aqueous phase is 6.8-7.0, and the organic phase is dried.

8. The application according to claim 4, characterized in that, In step S2, ammonia is used to adjust the pH of the mixed solution to 6.8-7.0; The aging method involves aging the mixed solution at 4-6℃ for 24 hours, followed by filtration to obtain crystals. The purification method involves washing the crystals 2-3 times with anhydrous ethanol and then drying them under vacuum.

9. A photosensitive solder resist ink, characterized in that, By weight, including individually packaged components A and B; Component A comprises 100-110 parts of oligomers containing carboxyl and acrylate groups, 5-7 parts of photoinitiator, 10-15 parts of acrylate monomer, 20-25 parts of talc, and 0.03-0.05 parts of polymerization inhibitor; the polymerization inhibitor is a copper-based complex with the structural formula shown in Formula 1. Formula 1, wherein R represents an alkylene group having 2 to 5 carbon atoms, an alkylene group having 2 to 5 carbon atoms with a methyl branch, an alkylene group having 2 to 5 carbon atoms with an ether bond, or an alkylene group having 2 to 5 carbon atoms with an ester bond; Component B consists of 4 to 8 parts of epoxy curing agent.

10. The photosensitive solder resist ink according to claim 9, characterized in that, The content of the polymerization inhibitor in component A is 50~500 ppm.